Advancements in peanut mechanization: Implications for sustainable agriculture - Moreira, Bruno Rafael de Almeida [UNESP]; Marra, Tulio Mazetti [UNESP]; Silva, Eduardo Arouche da; Brito Filho, Armando Lopes de [UNESP]; Barbosa Júnior, Marcelo Rodrigues [UNESP]; Santos, Adão Felipe dos; Silva, Rouverson Pereira da [UNESP]; Vellidis, George (Elsevier, 2024)
CONTEXT: Peanuts (Arachis hypogaea) hold significant global economic and nutritional importance, positioning them as a crucial crop in the realm of sustainable agriculture. In this comprehensive systematic and meta-analytic review, we thoroughly examine the extensive research and innovative strategies related to mechanizing peanut farming, with a specific focus on activities encompassing tilling, sowing, and harvesting. OBJECTIVE: Our primary aim is to provide a meticulous and analytical exploration of the far-reaching implications of mechanization in peanut production. We emphasize the urgent need for cost-effective, socially responsible, and environmentally sustainable practices. METHODS: Through a rigorous analysis of existing literature, we unveil the multifaceted impacts of mechanization on factors such as yield, quality, and losses in peanut cultivation. To ensure a comprehensive analysis, we primarily concentrated on peer-reviewed articles sourced from distinguished databases such as Scopus® and Web of Science™. Specifically, our review encompasses studies published between 1989 and 2022, covering a diverse collection of bibliographic resources. This range spans from the inception of the term “mechanizable peanut” to the most recent publications in these interdisciplinary databases. To refine our search, we developed research-specific search strings by combining relevant keywords, including “PEANUT”, “TILLAGE”, “SOWING”, “DIGGING”, “HARVESTING”, and/or “MATURITY”, along with appropriate Boolean operators. A team of reviewers meticulously evaluated the readability, consistency, and eligibility of papers by scrutinizing titles, highlights, abstracts, keywords, as well as materials and methods sections. We selectively included papers that aligned with our research scope, while excluding studies related to intercropping, rotation systems, fertilization, pests and diseases, and manual labor-related operations. RESULTS AND CONCLUSIONS: Our findings highlight the potential for increased productivity and quality in agricultural systems that embrace mechanization, all while minimizing losses and their environmental impact. To optimize yield and quality while reducing losses, it is imperative for stakeholders to collaborate and endorse conservationist tillage practices, precision sowing techniques, and advanced harvesting methods. SIGNIFICANCE: This meta-review serves as a call to action directed at the scientific community, policymakers, and producers, urging them to prioritize the integration of mechanization into peanut farming. This approach not only advances sustainable agricultural practices but also addresses the growing global demand for this essential crop. By examining advancements in conservationist tillage, precision sowing, and harvesting methodologies, we equip stakeholders with the knowledge required to enhance peanut cultivation. We particularly emphasize the importance of harnessing cutting-edge technologies, such as remote sensing for maturity prediction, to facilitate informed decision-making in the field.
Keywords: Arachis hypogaea; Conservationist tillage; Precision harvesting; Remote sensing; Sowing; Sustainable agriculture